Digital literacy for dummies user basics course. Setting up an Internet connection and troubleshooting (Hoboken, NJ : John Wiley & Sons, 2017)
After you have an Internet Service Provider, you can then connect to the Internet. This video shows you how to connect and then troubleshoot any problems.
Title from resource description page (viewed August 15, 2018).
In English.
Keywords: Internet; Internet literacy; Debugging in computer science; Computers -- Maintenance and repair; Computer literacy; Internet; Computer Literacy; Internet; Cyberculture; Débogage.; Connaissances en informatique; Internet; Computer literacy; Computers -- Maintenance and repair; Debugging in computer science; Internet; Internet literacy; Instructional films; Instructional films; Films de formation